PENGARUH DOSIS DAN CARA PENEMPATAN PUPUK NPK TERHADAP TERTUMBUHAN DAN HASIL JAGUNG HIBRIDA ( Zea mays. L ) INFLUENCE OF DOSAGE AND WAY OF LOCATION OF MANURE OF NPK TO GROWTH AND RESULT MAIZE OF HIBRIDA ( Zea mays. L ) - Moh. Taufik Moh. Taufik; AF Aziez AF Aziez; Tyas Soemarah KD Tyas Soemarah KD (Fakultas Pertanian, Universitas Tunas Pembangunan Surakarta, 2010)
Research is done in countryside of Kedokan Sayang of District Of Tarub Sub Province Tegal, with height of place + 25 m above sea surface at land ground type of alluvial. Research is done from 16 Februari 2008 until 8 June 2008, using factorial method with elementary pattern of RCBD (Randomized Completely Block Design) consist of 2 treatment factor that is : (1) Dose Fertilize NPK (D0 = without manure) (D1 = 150 kg/ha) (D2 = 300 kg / ha) (D3 = 450 kg/ha). (2) Way of location of manure ( C1 = disseminated) (C2 = Disseminated and countersinked) (C3 = make off with). Result of research show = (1) treatment of dose fertilize NPK have very significant at all of parameter that is is : High [of] crop, amount of leaf, heavy all is wet weight overall of crop, heavy run dry weight overall of crop, long cob, amount of seed of per cob, amount of making off with per cob, heavy dry minner per plant, heavy of dry minner of per check and heavy 100 seed. Heavy highest per check minner reached at dose 450 kg/ha that is 6,147 and low without manure that is 2,393 kg (2) treatment of location of manure show very significant at wet heavy parameter of overall of crop, heavy run dry weight overall of crop, and seed amount of per cob. While to amount make off with per cob give significant. weight of minner dry of highest per check reached at way of location of manure by disseminated and countersinked by that is 4,982 kgs, lowest by disseminated that is 4,730 kgs. (3) interaction among dose fertilize NPK by location of manure have very significant at parameter of is amount of leaf, wet heavy of overall of crop, heavy run dry weight overall of crop, long of cob, amount of seed of per cob and heavy 100 seed. While to amount make off with per cob give significant. (4) weight of minner highest drought of per check reached at combination of fertilizer dose NPK 450 kg/ha by the way of fertilisers placement disseminated and countersinked, that is 6,260 kgs ( 11128,819 kg/ha). While low at combination without fertilizer by the way of its(the fertilisers placement disseminated that is 2,120 kgs ( 3768,865 kg/ha).